2017
DOI: 10.1097/01.ogx.0000521121.90909.ff
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Transcranial Direct-Current Stimulation in Women With Provoked Vestibulodynia

Abstract: Short title: Brain stimulation in women with vestibulodynia. Condensation: Transcranial brain stimulation does not reduce pain intensity during intercourse in women with provoked vestibulodynia compared to sham stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Three of these studies did not randomly allocate participants to groups (Cummiford 2016; Lindholm 2015; Yoon 2014). Six were not clearly in a chronic population (Bolognini 2015; Choi 2014; Khedr 2005; Ma 2015; Morin 2017; Schabrun 2014), two were not studies of electrical brain stimulation (Maestu 2013; Smania 2005), one did not employ a sham control (Seada 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these studies did not randomly allocate participants to groups (Cummiford 2016; Lindholm 2015; Yoon 2014). Six were not clearly in a chronic population (Bolognini 2015; Choi 2014; Khedr 2005; Ma 2015; Morin 2017; Schabrun 2014), two were not studies of electrical brain stimulation (Maestu 2013; Smania 2005), one did not employ a sham control (Seada 2013).…”
Section: Resultsmentioning
confidence: 99%
“…May not be exclusively chronic painBelci 2004Pain is not measured as an outcomeBolognini 2013Inclusion of acute and chronic pain patientsBolognini 2015Not clearly a chronic populationCarraro 2010Not a study of electrical brain stimulationChoi 2012bStudy of acute painChoi 2012aStudy of acute painChoi 2014Not clearly a chronic populationCummiford 2016Allocation not randomisedEvtiukhin 1998A study of postoperative pain. No sham control employedFrentzel 1989Not a study of brain stimulationHargrove 2012bUncontrolled long‐term follow‐up data from Hargrove 2012aJohnson 2006Self‐reported pain is not measuredKatz 1991Study not confined to chronic painKhedr 2015Not clearly a chronic populationLindholm 2015Allocation not randomisedLongobardi 1989Not clearly studying chronic painMa 2015Not clearly a chronic populationMaestu 2013Not electrical brain stimulation ‐ magnetic fields unlikely to induce electrical currentsMorin 2017Not clearly a chronic pain population ‐ provoked vestibulodyniaNelson 2010Intervention not designed to alter cortical activity directly by electrical stimulation ‐ a neuro feedback interventionO'Connell 2013Not a RCT or quasi‐RCT ‐ no randomisation specifically to treatment group or orderPujol 1998Participants are a mixture of acute and chronic pain patientsSchabrun 2014Not clearly a chronic populationSeada 2013No sham control employed…”
Section: Characteristics Of Excluded Studies [Ordered By Study Id]mentioning
confidence: 99%
“…55 In a 2-week RCT, the effect of transcranial electric stimulation vs sham stimulation for PVD was investigated. 56 The intervention is a non-invasive method using direct current towards specific areas of the brain in an attempt to reduce pain during intercourse. None of the studies found any significant differences for variables related to pain, sexual satisfaction, anxiety or depression between the study groups (Table 6).…”
Section: Other Treatmentsmentioning
confidence: 99%
“…[7] Central neuromodulation, such as transcranial direct current stimulation (tDCS), alleviates pain by producing microcurrents that promote neuronal excitability and activate descending inhibition systems. [49] PTNS was performed by inserting a 34-gauge needle approximately 3 to 4 cm above the medial malleolus and 1 cm posterior to the tibia, along the running direction of the tibial nerve, placing the adhesive electrode on the medial heel, and then adjusting the stimulation amplitude, typically 30 min per session for consecutive 12 weeks. [47,50,51] A prospective study showed that PTNS could decrease pain and improve quality of life in women with CPP.…”
Section: Neuromodulationmentioning
confidence: 99%
“…[ 7 ] Central neuromodulation, such as transcranial direct current stimulation (tDCS), alleviates pain by producing microcurrents that promote neuronal excitability and activate descending inhibition systems. [ 49 ]…”
Section: Introductionmentioning
confidence: 99%